Prevalence of Staphylococcus aureus protein A (spa) mutants in the community and hospitals in Oxfordshire. - Votintseva, A; Fung, R; Miller, R; Knox, K; Godwin, H; Wyllie, D; Bowden, R; Crook, D; Walker, A (BioMed Central, 2014)
BACKGROUND: Staphylococcal protein A (spa) is an important virulence factor which enables Staphylococcus aureus to evade host immune responses. Genotypes known as "spa-types", based on highly variable Xr region sequences of the spa-gene, are frequently used to classify strains. A weakness of current spa-typing primers is that rearrangements in the IgG-binding region of the gene cause 1-2% of strains to be designated as "non-typeable". RESULTS: We developed an improved primer which enabled sequencing of all strains, containing any type of genetic rearrangement, in a large study among community carriers and hospital inpatients in Oxfordshire, UK (6110 isolates). We identified eight novel spa-gene variants, plus one previously described. Three of these rearrangements would be designated "non-typeable" using current spa-typing methods; they occurred in 1.8% (72/3905) asymptomatically carried and 0.6% (14/2205) inpatient S. aureus strains. Some individuals were simultaneously colonized by both formerly non-typeable and typeable strains; previously such patients would have been identified as carrying only currently typeable strains, underestimating mixed carriage prevalence and diversity. Formerly non-typeable strains were found in more spa-types associated with multilocus sequence type ST398 (35%), common among livestock, compared to other groups with any non-typeable strains (1-4%), suggesting particular spa-types may have been under-represented in previous human studies. CONCLUSIONS: This improved method allows us to spa-type previously non-typeable strains with rearrangements in the spa-gene and to resolve cases of mixed colonization with deletions in one or more strains, thus accounting for hidden diversity of S. aureus in both community and hospital environments.